2014
DOI: 10.1111/aphw.12035
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Trends in Eating Self-Regulation and Dietary Intake in Adolescents

Abstract: Background: Research suggests that while capacities for self-regulation gradually improve during adolescence, eating habits become unhealthier. This study investigated whether there are age-related patterns in using self-regulation strategies (SRS) as well as in the self-reported dietary intake of fruit, vegetables, and unhealthy snacks. Moreover, we tested the strength of the relationship between different SRS (aimed at goal versus aimed at temptations) and dietary intake across different ages in adolescents.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 37 publications
(40 reference statements)
1
21
0
2
Order By: Relevance
“…Peak muscle and bone mass as well as cardio-respiratory tness are reached during adolescence, and these physiological processes are both nutritionally sensitive and predictive of later health (15)(16)(17). In addition, widespread brain re-modelling during adolescence leads to a large increase in cognitive ability (18).…”
Section: Background and Rationalementioning
confidence: 99%
“…Peak muscle and bone mass as well as cardio-respiratory tness are reached during adolescence, and these physiological processes are both nutritionally sensitive and predictive of later health (15)(16)(17). In addition, widespread brain re-modelling during adolescence leads to a large increase in cognitive ability (18).…”
Section: Background and Rationalementioning
confidence: 99%
“…Though the ability to self-regulate improves during adolescence, the motivation to employ self-regulatory abilities for health-related practices declines during this period with implications for overall oral health and wellbeing [8,9]. This decline may be worse for adolescents and youths who live without parental influence and control, such as street-involved young persons (SIYP).…”
Section: Introductionmentioning
confidence: 99%
“…Clark & Zimmerman 24 proposed a model on how people use these skills to self-regulate their health, and to prevent or control disease, and several studies have shown that self-regulatory skills benefit health behavior in adolescents, for example, healthy eating. [25][26][27] However, as far as we know, no studies have focused on the relationship between self-regulatory skills and the incidence of overuse injuries. The goal of the current study is to investigate this relationship.…”
Section: Introductionmentioning
confidence: 99%